1986
DOI: 10.1159/000138202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanical Stimulation, Substance P and Vasoactive Intestinal Polypeptide on the Electrical and Mechanical Activities of Circular Smooth Muscles from Pig Coronary Arteries Contracted with Acetylcholine: Role of Endothelium

Abstract: Mechanical stimulation, substance P and vasoactive intestinal polypeptide (VIP) were found to relax the transversal strip of anterior descending branches of pig coronary arteries precontracted by acetylcholine. The effects of mechanical stimulation and substance P required the presence of intact endothelium, while VIP did not. The effect of VIP did not appear to be mediated by catecholamines. Simultaneous measurements of intracellular membrane potential and tension developed by coronary smooth muscle precontra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 12 publications
5
38
0
Order By: Relevance
“…The hyperpolarization induced by ACh was transient and ceased within several minutes. Such hyperpolarization and sustained relaxation also occurred in the pig coronary artery (Beny et al, 1986) and in the rat aorta (Southerton et al, 1987). Furthermore, Komori & Suzuki (1987a) observed that although both ACh and oxotremorine cause release of EDRF and relax the precontracted rabbit saphenous artery, only ACh hyperpolarizes the membrane.…”
Section: Discussionmentioning
confidence: 92%
“…The hyperpolarization induced by ACh was transient and ceased within several minutes. Such hyperpolarization and sustained relaxation also occurred in the pig coronary artery (Beny et al, 1986) and in the rat aorta (Southerton et al, 1987). Furthermore, Komori & Suzuki (1987a) observed that although both ACh and oxotremorine cause release of EDRF and relax the precontracted rabbit saphenous artery, only ACh hyperpolarizes the membrane.…”
Section: Discussionmentioning
confidence: 92%
“…Some agents which induce endothelium-dependent vasorelaxation are known to induce simultaneously endothelium-dependent membrane hyperpolarization of smooth muscle cells, and there have also been reports discussing whether or not SP induces endothelium-dependent membrane hyperpolarization of smooth muscle cells. SP is known to induce hyperpolarization and relaxation of vascular smooth muscles, including the porcine coronary artery (Beny et al, 1986;Pacicca et al, 1992;Zhang et al, 1994), although in certain types of tissue, SP relaxes the arteries in the absence of any changes in the membrane potential (Bolton & Clapp, 1986). Chen & Suzuki (1989) reported that hyperpolarization is generated by an increase in K+ conductance of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Today, endothelium-dependent relaxation is considered to be produced by, at least, three factors: PG12, EDRF and EDHF. Substance P (SP) induces an endothelium-dependent va-sorelaxation. There have been reports of SP-induced endothelium-dependent hyperpolarization of smooth muscle cells (Beny et al, 1986;Pacicca et al, 1992 (Di Virgilho et al, 1989) and 5% foetal bovine serum for 1.5 h at 370C (Aoki et al, 1994). After loading with fura-2, both vascular and valvular strips were incubated in normal PSS for at least 1 h before starting the measurement, in order to remove the dye in the extracellular space and for purposes of equilibration.…”
Section: Introductionmentioning
confidence: 99%
“…obtained post mortem contract to acetylcholine. 58 Furchgott and Zawadzki 165 have pointed out that retention of even only a few percent of the endothelial cells allows substantial expression of relaxation. Constriction of the human arteries in vitro to acetylcholine in the presence or absence of endothelium has now been confirmed by others, 168 as has the stability of responses in postmortem coronary tissue up to 8 hours after death.…”
Section: Glml Added In Perfusion Reservoir) Of Vasoconstrictor Respomentioning
confidence: 99%